Brain potential response to activation procedures in children with refractive amblyopia (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To identify the features of cortical potential response to activation procedures in patients with mild and moderate refractive amblyopia.Material and Methods: We examined electroencephalography (EEG) response to activation procedures (specifically, eye opening and photic stimulation) in 22 pediatric amblyopes and 15 healthy children. All subjects underwent an eye examination, including visual acuity measurement, ophthalmoscopy, and refractometry. In addition, binocular function was assessed using the Worth 4-dot test and synoptophore. An EEG response to alternating unilateral eye opening was used as an indicator of the integrity of the prechiasmal pathway. A response to 10-Hz rhythmic photic stimulation (rhythmic driving response, RDR) was used as a measure of maturity of cortical neurons. The performance of the thalamocortical relay was assessed through the RDR to unilateral and bilateral photic stimulation with the eyes closed to exclude the effect of reticular formation. In addition, eyes closed EEG synchronization was assessed at symmetric EEG derivations to detect the absence of connection through the corpus callosum.Results: In the total sample of children with mild and moderate refractive amblyopia, there was an increased rate of a weak desynchronization response to bilateral eye opening and to unilateral eye opening in the hemisphere ipsilateral to the amblyopic eye. Particularly, a weak response was exhibited by all patients without binocular vision. In addition, we found the absence of slow waves in both hemispheres during rhythmic driving response to binocular photic stimulation and during response to bilateral eye opening. Conclusion: Findings of this study (1) evidence immaturity of cortical and midbrain neurons and (2) confirm the integrity of the major retinal cortical pathway and retinal thalamic cortical pathway and their interhemispheric connection in children with mild and moderate refractive amblyopia.
Keywords: refractive amblyopia; brain potential; electroencephalography; EEG